A single-dose mRNA vaccine provides a long-term protection for hACE2 transgenic mice from SARS-CoV-2 - Qingrui Huang (Nature Portfolio, 2021)
Several mRNA-based vaccines for SARS-CoV-2 are in late phase clinical development. Here, the authors show that a single immunization with a mRNA vaccine expressing SARS-CoV-2 spike RBD induces neutralizing antibodies that are maintained for at least 6.5 months and confer protection in a sera transfer study in mice.